Impaired Attentional Processing During Parabolic Flight - Friedl-Werner, Anika; Machado, Marie-Laure; Balestra, Costantino; Liegard, Yannick; Philoxene, Bruno; Brauns, Katharina; Stahn, Alexander C.; Hitier, Martin; Besnard, Stephane (Frontiers in Physiology, 2021)
Previous studies suggest that altered gravity levels during parabolic flight maneuvers affect spatial updating. Little is known about the impact of the experimental setting and psychological stressors associated with parabolic flight experiments on attentional processes. To address this gap, we investigated the level of alertness, selective and sustained attention in 1 and 0 g using a Go/No-Go paradigm in form of a Continuous Performance Task. Additionally, we assessed parameters associated with the experimental set-up of a parabolic flight that we expected to impact attentional processing such as the routine use of scopolamine, sleep quality, and participant’s stress level, as well as mood and anxiety state before and after parabolic flight exposure. We observed a deterioration in attentional processing prior to the first parabola that was further aggravated in weightlessness and returned to baseline after the last parabola. Reaction Time, Hit and False Alarm Rate were moderately correlated with self-reported anxiety state, but not cortisol levels or other emotional states. The use of scopolamine had minor effects on Reaction Time. Our results point out important aspects that should be considered for the design of behavioral research experiments in future parabolic flight campaigns.